The end of poverty : economic possibilities for our time - Sachs, Jeffrey D., (Penguin Press, 2005)
"Hailed by Time as one of the world's 100 Most Influential People, Jeffrey Sachs is world renowned for his work around the globe advising economies in crisis. He has advised a broad range of world leaders and international institutions on the challenges of hyperinflation, disease, post-communist transition, and extreme poverty. Now, at last, he draws on all he has learned from twenty-five years of work to offer a uniquely informed vision of the keys to economic success in the world today and the steps that are necessary to achieve prosperity for all.